Assessment of the antigenotoxic activity of white sesame extract (Sesamum indicum) against vincristine induced genotoxicity in mice - diab, kawthar Abdel Aziz; Hassan, Zeinab Mohamed (Comunicata Scientiae, 2011)
White sesame seeds, used as an oilseed since ancient time, contain 25% protein and 50% oil, the latter have unique chemical and physiological activities. In view of its important biological activity, this study was performed to evaluate the efficacy of sesame oil (SO) to protect mice against vincristine (VCR) induced genotoxicity using different endpoints. Chromosomal aberrations (CAs) in bone marrow cells and in spermatocytes as well as morphological sperm abnormalities were determined in the tested animals. Mice were orally treated (using a stomach tube) with SO for 7 consecutive days. Vincristine was used as a mutagenic agent and was given intraperitoneally at a single dose of 0.5 mg/kg b.w, 24 hr after last dose of SO. The results clearly showed that SO tested at high dose (400 mg/mouse) didn’t induce any genotoxic effect. Pretreatment with the three tested doses of SO (100,300 and 400 mg/mouse) to VCR-treated mice significantly minimized CAs in bone marrow cells and spermatocytes. Morphological sperm abnormalities decreased significantly after treatment with SO. It could be concluded that, intake of dietary SO may be considered a promising approach toward reducing the genotoxicity induced by chemotherapeutic agent VCR. Accordingly, sesame seeds and its components may be exploited commercially for pharmaceutical purposes.